A rapid protocol to distinguish between Citri Exocarpium Rubrum and Citri Reticulatae Pericarpium based on the characteristic fingerprint and UHPLC-Q-TOF MS methods. Issue 4 (20th April 2020) - Shi, Liqiang; Wang, Rongjin; Liu, Tianshu; Wu, Jiajie; Zhang, Hongxu; Liu, Zhiqiang; Liu, Shu; Liu, Zhongying
Abstract : Citri Exocarpium Rubrum and Citri Reticulatae Pericarpium were successfully distinguished by the characteristic fingerprint and UHPLC-Q-TOF MS methods. Abstract : Citri Exocarpium Rubrum (CER) and Citri Reticulatae Pericarpium (CRP) are used as common functional foods and traditional Chinese medicine (TCM). As different parts of the same fruit, CER and CRP have different effects in clinical applications. However, they are commonly confused due to the similarity of the chemical compounds and a lack of scientific method to distinguish them in the finished product. In this study, an ultra-high performance liquid chromatography-diode array detector (UHPLC-DAD) technique and an ultra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF MS) method were employed to generate the characteristic fingerprint under the optimum analytical conditions. Principal component analysis (PCA) and orthogonal partial least squares discrimination analysis (OPLS-DA) were applied to represent different chemical markers for CER and CRP. 44 potential markers including 15 polymethoxylated flavanones (PMFs), 5 flavone- C -glycosides, 6 flavanone- O -glycosides, 3 flavonoid- O -glycosides, 8 organic acids, 5 limonoids and 2 alkaloids were successfully identified by using UNIFI software. The heat map showed that there were significant differences in the CER and CRP samples. Furthermore, 12 potential markers were screened out by characteristic fingerprint and UHPLC-Q-TOF MS methods and were analyzed by quantitative analysis of multicomponents by a single marker (QAMS) method. Finally, a prediction model based on the discovered chemical markers was established for discrimination between CER and CRP. Using these markers can significantly distinguish the unknown processed products of CER and CRP. In conclusion, an effective way to quickly and easily distinguish CER and CRP was successfully established based on the characteristic fingerprint and UHPLC-Q-TOF MS. It could also be a new strategy for analysis of different processed products of the same plant source.